Secondary metabolites of the lichen-associated fungus Apiospora montagnei. Issue 17 (26th April 2017) - Wang, Hao; Umeokoli, Blessing O.; Eze, Peter; Heering, Christian; Janiak, Christoph; Müller, Werner E.G.; Orfali, Raha S.; Hartmann, Rudolf; Dai, Haofu; Lin, Wenhan; Liu, Zhen; Proksch, Peter
Graphical abstract: Highlights: The endolichenic fungus Apiospora montagnei yielded three new compounds. X-ray diffraction analysis was performed for1, the first seco -libertellenone. Several compounds exhibited significant cytotoxicity against L5178Y cell line. Abstract: The endolichenic fungus Apiospora montagnei isolated from the lichen Cladonia sp. was cultured on solid rice medium, yielding the new diterpenoid libertellenone L (1 ), the new pyridine alkaloid, 23- O -acetyl- N -hydroxyapiosporamide (2 ) and the new xanthone derivative 8-hydroxy-3-hydroxymethyl-9-oxo-9 H -xanthene-1-carboxylic acid methyl ether (3 ) together with 19 known compounds (4 –22 ). The structures of the new compounds were elucidated by 1D and 2D NMR spectra as well as by HRESIMS data. The absolute configuration of the new 6, 7- seco -libertellenone derivative1 was determined by single-crystal X-ray diffraction. Four additional known compounds23 –26 were isolated when NaCl or NH4 Cl were added to solid rice medium. Compounds7 –9, 18 and26 exhibited significant cytotoxicity against the L5178 murine lymphoma cell line with IC50 values of 2.6, 0.2, 2.1, 2.7 and 1.7 μM, respectively.